THE EXODUS OF ETHIOPIAN REFUGEES IN SUDAN: A STUDY OF THE ROLES AND RESPONSIBILITIES OF HOST COUNTRIES - Ahsani Maulinardi; Yon Machmudi; Sri Yunanto (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2022)
The Government of Sudan hastened to handle refugees when a mass influx of Tigrayan refugees swarmed the Ethiopian-Sudanese border in late 2020. Political rivalry between the TPLF (Tigray People’s Liberation Front) and the coalition led by Ethiopian PM Abiy Ahmed's newly formed political coalition Prosperity Party/Paartii Badhaadhiina reached an all-time high when Federal Government decided to halt the financial aid planned for Tigray and formally reject regional election results held by Tigray earlier in September 2020; PM Abiy Ahmed condemned it as an illegal election carried out without Federal Government’s approval. In countermeasure, TPLF stormed the Ethiopian Defense Force regional base headquartered in Tigray capital, Mekelle, An action that provoked PM Abiy Ahmed's intentions to crush the TPLF once and for all. The military coalition consisted of Ethiopian Defense Force, Amhara Milita the Liyu Hayl, and Eritrean forces attacked Tigray from two consecutive fronts, forcing the civilians to flee their homes west into the Ethiopian-Sudanese border, begging for asylum from the Sudanese Government. This study aims to answer the roles and responsibilities carried out by the Sudanese Government in handling the Ethiopian refugees sheltered in the states of Kassala, Gedaref, and Blue Nile during the Tigray crisis. Using Kayongo-Male’s African Refugee Migration research model, the authors find the eagerness shown by the Sudanese Government to handle the Ethiopian refugees, the difficulties of rehabilitating the infrastructure, and the passive role of the African Union in mediating the conflict between the TPLF and Federal Ethiopian Government.